Digital and online symptom checkers and health assessment/triage services for urgent health problems: systematic review. Issue 8 (1st August 2019) - Chambers, Duncan; Cantrell, Anna J; Johnson, Maxine; Preston, Louise; Baxter, Susan K; Booth, Andrew; Turner, Janette
Abstract : Objectives: In England, the NHS111 service provides assessment and triage by telephone for urgent health problems. A digital version of this service has recently been introduced. We aimed to systematically review the evidence on digital and online symptom checkers and similar services. Design: Systematic review. Data sources: We searched Medline, Embase, the Cochrane Library, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Health Management Information Consortium, Web of Science and ACM Digital Library up to April 2018, supplemented by phrase searches for known symptom checkers and citation searching of key studies. Eligibility criteria: Studies of any design that evaluated a digital or online symptom checker or health assessment service for people seeking advice about an urgent health problem. Data extraction and synthesis: Data extraction and quality assessment (using the Cochrane Collaboration version of QUADAS for diagnostic accuracy studies and the National Heart, Lung and Blood Institute tool for observational studies) were done by one reviewer with a sample checked for accuracy and consistency. We performed a narrative synthesis of the included studies structured around pre-defined research questions and key outcomes. Results: We included 29 publications (27 studies). Evidence on patient safety was weak. Diagnostic accuracy varied between different systems but was generally low. Algorithm-based triage tended to be more risk averse than that of health professionals. There was very limited evidence on patients' compliance with online triage advice. Study participants generally expressed high levels of satisfaction, although in mainly uncontrolled studies. Younger and more highly educated people were more likely to use these services. Conclusions: The English 'digital 111' service has been implemented against a background of uncertainty around the likely impact on important outcomes. The health system may need to respond to short-term changes and/or shifts in demand. The popularity of online and digital services with younger and more educated people has implications for health equity. PROSPERO registration number: CRD42018093564.